COVID-19 gastrointestinal manifestation presenting as acute surgical like abdomen - Ramavath, Krishna; Rao, Siddharth S.; Sindhu, Nyna; Parmeshwar, Tushar; Palle, Pranay (International Surgery Journal, 2021)
COVID-19 disease is caused by severe acute respiratory syndrome corona virus-2 (SARS-CoV-2) which can cause respiratory symptoms more. It can cause gastrointestinal symptoms also due to this RNA virus protein binding to the angiotensin converting enzyme 2 (ACE2) receptors which are abundantly present in stomach, small intestine, large intestine and liver. The gastrointestinal manifestations of COVID-19 disease can present as acute surgical abdomen which can create diagnostic dilemma. We presented a case of COVID-19 disease, admitted in our hospital. Later he had symptoms of acute surgical abdomen symptoms like sudden onset abdominal pain, nausea, vomiting and loose stool without blood. He was properly evaluated and conservatively managed. The gastrointestinal manifestations of COVID-19 disease can present as acute surgical abdomen. So, these patients properly evaluated and then only surgical plan will be made according pathology.